Da arquitetura à não-arquitetura: Gordon Matta-Clark e Rachel Whiteread - Goncalves, Simone Neiva Loures (2019)
The research is based on the hypothesis that in the recent encounter between art and architecture, termed "complex" by Hal Foster, a field of more positive relations arises than those pointed out by Rosalind Krauss in 1979. The goal of the research is to understand how the works of artists Gordon Matta-Clark and Rachel Whiteread situated in the category “axiomatic structures” (architecture / non-architecture) – have resulted in more positive relations. The proposed study on the dialogue between art and architecture is limited by the notion of extended field proposed by Krauss in 1979 in the article Sculpture in the Expanded Field and the complexity of the relation between both disciplines, observed by the critic Foster in his book The Art Architecture Complex, published in 2011.